TEOLOGI KRISTEN SEBAGAI FONDASI SPIRITUAL DALAM MEMBENTUK IMAN, KARAKTER, DAN KEPEMIMPINAN ORANG PERCAYA DI TENGAH PERUBAHAN ZAMAN - Miska Rahayu EK; Yesintia Nugraha Wilani; Nita Datu Langi; Malvionita Palimbunga; Yunial Riri' (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2026)
Christian theology is an essential spiritual foundation for shaping the faith, character, and leadership of believers amidst changing times marked by developments in science, technology, and socio-cultural dynamics. This article aims to examine the role of Christian theology as the foundation for building a solid faith, Christian character that reflects divine values, and spiritual leadership oriented toward God's will. The method used in this research is a qualitative method with a literature study approach, namely analyzing various relevant Christian theological literature to understand the function and implications of theology in the lives of believers. The results of the discussion indicate that Christian theology provides an epistemological, moral, and spiritual foundation that helps believers understand their identity, calling, and purpose in life. Theology also plays a role in shaping character through spiritual transformation and renewal of thought centered on God's Word. Furthermore, theology is the foundation for spiritual leadership that is imbued with integrity, service, and responsibility. Amid changing times, theology remains relevant because it provides direction, hope, and stability of faith.